1990
DOI: 10.1159/000125533
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically Significant Inhibitory Hypothalamic Action of Substance P on Prolactin Release in the Male Rat

Abstract: To evaluate a possible physiological role of endogenous substance P (SP) in the control of prolactin (PRL) release, conscious adult male rats were given injections of a specific antiserum against SP (anti-SP) into the third ventricle (3 µl) or intravenously (0.5 ml). Third-ventricular injection of anti-SP induced a significant increase in plasma PRL levels when compared to values in control animals injected with normal rabbit serum (p < 0.02). Plasma PRL concentrations were significantly elevated within 2 h af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Given that substance P is a key mediator of neurogenic skin inflammation [70], and may partially explain the effects of psychological stress on hair growth in alopecia areata and telogen effluvium [33], it is interesting to note that substance P decreased PRL IR. This is well in line with similar substance P effects reported on pituitary PRL production in rodents [71].…”
Section: Discussionsupporting
confidence: 92%
“…Given that substance P is a key mediator of neurogenic skin inflammation [70], and may partially explain the effects of psychological stress on hair growth in alopecia areata and telogen effluvium [33], it is interesting to note that substance P decreased PRL IR. This is well in line with similar substance P effects reported on pituitary PRL production in rodents [71].…”
Section: Discussionsupporting
confidence: 92%
“…Injection of SP into the third ventricle (Vijayan & McCann, 19796) or into the medial preoptic area (Picanco-Diniz, Valenca, Franci & Antunes- Rodrigues, 1990) resulted in increased concentrations of prolactin in rat plasma, and the former route of administration was also effective in primates (Eckstein, Wehrenberg, Louis et al 1980). However, recent work has demon¬ strated that, although higher doses of SP given intraventricularly can indeed stimulate the release of prolactin, inhibition can be induced by lower doses (Arisawa, Snyder, Yu et al 19906), and the same paradoxical pattern of prolactin response was observed following low or high intravenous doses of SP. Since it is improbable that SP can cross the blood-brain barrier, the evidence so far is weighted towards SP modulating the release of prolactin directly from anterior pituitary lactotrophs, although no increased plasma concentrations of pro¬ lactin following intravenous SP were observed in sheep (Thomas, Cummins, Griffin & Clarke, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Being stored in the secretroy vesicles of these cells [3], SP is synthesized de novo as verified by constitutive expression of preprotachykinin A mRNAs encoding the precursors of SP [4]. Moreover, the anterior pituitary cells bear specific membrane receptors of NK-1 type for SP [5,6], which justifies the widely observed yet diverse effects of SP on hormonal secretion from the anterior pituitary [7].…”
Section: Introductionmentioning
confidence: 89%